On summation of a class of Q-series - Denis, Remy (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
In the present work, the author shows must of the results of Pandey and Saram, Sharma and Srivastava on generalizations of some classical hypergeometric summation theorems for multiple hypergeometric series, are special cases of author's previous results.